Lukian w bizantyńskich podziemiach. Analiza i tłumaczenie centonu opartego na tekstach Lukiana - Marciniak, Przemysław (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
An anonymous Lucianic cento, modelled on the Dialogues of the Dead, was handed down in the manuscript Ambrosianus gr. 655. This article argues that the text might have been compiled in the 12th century when Lucian and his text not only enjoyed a considerable popularity but Lucianic writings were imitated by authors such as Theodoros Prodromos. What is more, it is suggested that this text might have been written for didactic purposes, perhaps as a kind of schedos. This articles offers also the first Polish and the second modern translation of the dialogue.